Insights into the Differential Composition of Stem-Loop Structures of Nanoviruses and Their Impacts - Aamir Lal; Amen Shamim; Eui-Joon Kil; Thuy T. B. Vo; Muhammad Amir Qureshi; Nattanong Bupi; Marjia Tabassum; Sukchan Lee (Microbiology Spectrum, 2023)
ABSTRACT Multipartite viruses package their genomic segments independently and mainly infect plants; few of them target animals. Nanoviridae is a family of multipartite single-stranded DNA (ssDNA) plant viruses that individually encapsidate ssDNAs of ~1 kb and transmit them through aphids without replication in aphid vectors, thereby causing important diseases in host plants, mainly leguminous crops. All of these components constitute an open reading frame to perform a specific role in nanovirus infection. All segments contain conserved inverted repeat sequences, potentially forming a stem-loop structure and a conserved nonanucleotide, TAGTATTAC, within a common region. This study investigated the variations in the stem-loop structure of nanovirus segments and their impact using molecular dynamics (MD) simulations and wet lab approaches. Although the accuracy of MD simulations is limited by force field approximations and simulation time scale, explicit solvent MD simulations were successfully used to analyze the important aspects of the stem-loop structure. This study involves the mutants’ design, based on the variations in the stem-loop region and construction of infectious clones, followed by their inoculation and expression analysis, based on nanosecond dynamics of the stem-loop structure. The original stem-loop structures showed more conformational stability than mutant stem-loop structures. The mutant structures were expected to alter the neck region of the stem-loop by adding and switching nucleotides. Changes in conformational stability are suggested expression variations of the stem-loop structures found in host plants with nanovirus infection. However, our results can be a starting point for further structural and functional analysis of nanovirus infection. IMPORTANCE Nanoviruses comprise multiple segments, each with a single open reading frame to perform a specific function and an intergenic region with a conserved stem-loop region. The genome expression of a nanovirus has been an intriguing area but is still poorly understood. We attempted to investigate the variations in the stem-loop structure of nanovirus segments and their impact on viral expression. Our results show that the stem-loop composition is essential in controlling the virus segments' expression level.